UMBILICAL CORD CARE – FACT AND FALLACIES – A REVIEW - Swapnil Raskar; Rajagopala S V K Kori; KS Patel (International Journal of Applied Ayurved Research, 2016)
Neonatal mortality and morbidity due to neonatal sepsis is a global burning health issue. Umbilical cord stump is a great source of infection for sepsis in newborn. Since very long time in modern era no any strong evidence based medicine has been introduced for umbilical cord care that which has global acceptance. Nowadays, in developed as well as developing countries dry care and application of some antimicrobial agents are in use. Till date health professionals are struggling with the standard cord care protocol which prevent the colonization of bacteria causing sepsis, protect the bacterial colonies useful for healing the wound after cord fall, help in early separation of cord and to prevents the future complications like omphalocoele. Ayurveda defines a standard protocol for neonatal care and umbilical cord care is explained as Nabhi Upakrama. The Nabhi Upakrama achieves the all above mentioned goals of umbilical cord care. Use of the topical medicine which are antimicrobial and wound healing such as Kushtha Taila and Jatyadi Taila are useful in umbilical cord care. This Nabhi Upakrama is scientific, time tested, safe and effective. Present article is an effort to promote the Ayurveda neonatal umbilical cord care practices to reduce the neonatal mortality and morbidity and globally mainstreaming the fundamentals of Ayurveda with today’s health care system.